The Potential of Acacia Auriculiformis Leaf Extracts as an Antifungal of Candida albicans and Identification of the Compounds - Sari, Ni Kadek Yunita; Sumadewi, Ni Luh Utari (Metamorfosa: Journal of Biological Sciences, 2019)
Infections caused by Candida albicans have been increased dramatically worlwide. Acacia auriculiformis is an Indonesian Indigenous plant which has limited use only for fiber needs, especially for paper industry raw materials and as a protective plant. The use of Acacia auriculiformis as a traditional medicine, especially as an antifungal, is rarely reported. The purpose of this study was to determine the potential of acacia leaf extract ( Acacia auriculiformis ) as an antifungal against Candida albicans growth and identification of its compound class. The potential of acacia leaf extract as antifungal was tested by Kirby-Bauer method using paper discs and identification of acacia leaf compound class was carried out by phytochemical test. The results showed that acacia leaf extract ( Acacia auriculiformis ) concentration of 1%, 5%, 10% have potential to be an antifungal against the growth of Candida albicans and the methanol extract compound of acacia leaves consists of saponins, tannins, alkaloids, flavonoids, steroids and phenolics. Keyword : Candida albicans , Acacia auriculiformis , antifungal